تأثير بعض معاملات كسر طور السكون على إنبات بذور الدبق Cordia myxa Forsk. وإكثاره بالعقل (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2017)
أجريت هذه الدراسة خلال عامي 2014– 2015 م في مشتل الجامعة (محافظة اللاذقية) و مشتل سلحب (ريف محافظة حماة) ،أخذت البذور من موقعين من محافظة اللاذقية ( مشقيتا وبسنادا) التي يوجد فيها الدبق Cordia myxa كنوع مدخل في بعض المناطق الساحلية وطبقت عليها ثلاث معاملات( الخدش ، نقع بالماء الجاري ، نقع بالماء المغلي) إضافةً للشاهد.أظهرت النتائج تأثير عملية خدش البذور على المعاملات المدروسة في الموقعين المختلفين وظهرت فروق معنوية في نسبة انبات البذور في كلا الموقعين حيث بلغت (55%) في مشتل الجامعة و(35%) في مشتل الغاب. بينما لم يكن هناك أي تباين بين معاملتي الماء المغلي والجاري فيما يتعلق بطاقة الانبات في موقع الغاب. معاملة الخدش أعطت أعلى طاقة انبات 25 % في مشتل الغاب و21.66 % في مشتل الجامعة غير أن نفس المعاملة قللت من سرعة الإنبات مقارنة مع باقي المعاملات في مشتل الجامعة ، حيث احتاجت البذرة بالمتوسط (8.01) يوم ، إلا أنها زادت من سرعة الانبات في مشتل الغاب إذ احتاجت البذرة (1.54) يوم. أخيراً فيما يتعلق بالعقل لم يسجل مشاهدة لأي أثر إيجابي للعقل المعاملة بهرمون الأندول بيوتريك أسيد بتركيز (1غ/ل) لمدة (30،20،10 دقيقة). يمكن الاستنتاج بأنه يوجد تغيرات في نسبة وطاقة وسرعة الانبات في كلا الموقعين تبدو وكأنها مؤشر أولي لتأثير بعض معاملات كسر طور السكون على المؤشرات المدروسة لنوع الدبق. This study was carried out during 2014-2015 in two different nurseries located in University nursery (Lattakia governorate) and Salhab nursery (countryside of Hama governorate). Seeds were taken from two sites of Lattakia governorate (Mashqita– Bsnada) where Cordia myxa exists as exotic species in some coastal regions and three treatments in addition to control were examined .The results showed that there is an effect of scarification of seeds on investigated treatments and were significant differences in germination percentage in both sites which recorded 55% in university nursery and 35% in Al-Ghab nursery. While there were not contrast between the soaking in boiling and tap water treatments on the seed germination energy in Al-Ghab nursery. Scarification treatment gave higher value of germination energy 25% in Al-Ghab nursery and 21.66% in university nursery , while the same treatment decreased germination velocity compared to other treatments in university nursery which seed needed in average ( 8,01 day) whereas the same treatment increased germination velocity in Al-Ghab nursery which needed (1,54 day). Finally, regarding to cutting ,There is not observe to any positive influence to cuttings which treated in ABA hormone (1g/l) for (10,20,30 m). It could be deduced that there were changes in germination percentage, germination energy and germination velocity in two sites which appeared to be a Preliminary indication of impact of the some dormancy breaking treatments on investigated indications of Cordia myxa Forsk. species .